TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN GULAKU DI KOTA BANDAR LAMPUNG - Vientika Anggraini; Fembriarti Erry Prasmatiwi; Hurip Santoso (Lampung University, 2013)
This study aims to determine the level of satisfaction and consumer loyalty of Gulaku in Bandar Lampung, and to know the effect of the marketing mix to the level of customer satisfaction and loyalty of Gulaku. This research was conducted in June 2012, involving 66 housewives. The study sites were 3 modern markets (Chandra, Giant, and Hypermart) and 3 tradisional markets (Kangkung, Way Halim, and Tugu). The analysis tools were Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), the analysis of switcher buyer, habitual buyer, satisfied buyer, liking the brand, committed buyer and structural equation models (SEM). The research result showed that the level of customer satisfaction of Gulaku in Bandar Lampung in the category of very satisfied with the value of CSI 81.86% categorized as loyal consumer. The average value of IPA for the level of performance of Gulaku was 3,98 and the level of interest of Gulaku was 4,08. Using SEM analysis, it showed that the marketing mix did not significantly affect the level of customer satisfaction and customer loyalty of Gulaku. Keywords: CSI, customer, gulaku, IPA, loyalty, satisfaction, SEM